Knowledge, Attitude and Practices (KAP) regarding hearing health and noise-induced hearing loss among folk/light music professionals from Chennai (International Journal of Occupational Safety and Health, 2024)
Introduction: Musicians are exposed to music at high intensities and are at risk for developing noise- induced hearing loss (NIHL). Since hearing is so important to their career, they deserve special consideration. To avoid the deleterious effects of loud music, the professionals should be sensitized to the noise exposure and the use of strategies to prevent NIHL. The aim of the study is to determine the knowledge and attitude towards noise induced hearing disorders, and hearing conservative practices among professional musicians.Method: A KAP questionnaire was administered online to 136 professional musicians belonging to folk/ light music genre in Chennai. The participants were 115 males and 21 females, ranging in age from 18 to 75 years with the mean age of 29 (SD= 11).Results: The findings revealed that musicians were aware of the nature and cause of NIHL, but knowledge of NIHL prevention and treatment was limited to few. They had common misconceptions about the sources of harmful loud sounds, the effects of hearing loss, and hearing conservation strategies. Only a few participants reported to have used Ear Protective Devices (EPDs). Conclusion: Although musicians are aware of the risks of exposure to loud noise, they seldom use hearing protection. It is therefore vital to provide crucial information regarding NIHL and its prevention and promote musicians for better hearing preservation practices.